2023
DOI: 10.1371/journal.pone.0283213
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement status of registered nurses in pediatric units in Saudi Arabia: A cross‐sectional study

Abstract: Background This study aimed to evaluate the work engagement status of registered pediatric nurses and its relationship with personal- and work-related variables in selected hospitals. Personal- and work-related factors generally influence work engagement. However, data on work engagement in pediatric clinical practice are limited. Methods This study employed a cross-sectional design, including 230 registered nurses working in pediatric units in Madinah, Saudi Arabia. A non-probability approach (convenience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
(49 reference statements)
1
14
2
Order By: Relevance
“…Yang, Hatanaka, Takahashi, Shimizu 34 revealed that the group with a university degree or higher has significantly lower scores on work engagement than those with diplomas. Alharbi, Alrwaitey 25 showed higher educational levels align with higher work engagement. Allande-Cussó, García-Iglesias, Ruiz-Frutos, Domínguez-Salas, Rodríguez-Domínguez, Gómez-Salgado 29 and Borges, Sequeira, Queirós, Mosteiro‐Díaz 27 called the educational level equal to the academic training level.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Yang, Hatanaka, Takahashi, Shimizu 34 revealed that the group with a university degree or higher has significantly lower scores on work engagement than those with diplomas. Alharbi, Alrwaitey 25 showed higher educational levels align with higher work engagement. Allande-Cussó, García-Iglesias, Ruiz-Frutos, Domínguez-Salas, Rodríguez-Domínguez, Gómez-Salgado 29 and Borges, Sequeira, Queirós, Mosteiro‐Díaz 27 called the educational level equal to the academic training level.…”
Section: Resultsmentioning
confidence: 88%
“…Socio-demographic characteristics are the inherent personal attributes of nurses that describe their social and demographic characteristics. These characteristics are not easily changed and include 14 factors from our review based on 13 studies, such as age, 23–27 gender, 27–31 marital status, 32 , 33 educational level, 25 , 34 physical condition, 28 monthly income, 30 number of children, 35 years of experience, 23 , 25–27 , 34 position at work, 23 , 28 , 32 , 33 employment status, 23 , 27 , 33 years in the present unit, 23 and nationality 25 , 27 ( Table 2 ). Socio-demographic characteristics can provide insights into broad trends or disparities within a group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations